2015
DOI: 10.1038/srep16038
|View full text |Cite
|
Sign up to set email alerts
|

Family history of esophageal cancer increases the risk of esophageal squamous cell carcinoma

Abstract: A population-based case-control was performed to explore familial aggregation of esophageal squamous cell carcinoma (ESCC). Family history of cancer was assessed by a structured questionnaire, and from which 2 cohorts of relatives of cases and controls were reconstructed. Unconditional logistic regression and Cox proportional hazards regression were applied for case-control design and reconstructed cohort design, respectively. We observed a close to doubled risk of ESCC associated with a positive family histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 25 publications
1
71
0
Order By: Relevance
“…According to data from the local Cancer Registry, there are approximately 640 esophageal cancer cases in the 40‐ to 85‐year‐old age group annually (the crude rate in Taixing was 60.67 per 100,000). The study subjects were restricted to local inhabitants (Chinese Han race) aged 40–85 years who had lived in Taixing for at least 5 years prior to the diagnosis date for cases or the interview date for controls …”
Section: Methodsmentioning
confidence: 99%
“…According to data from the local Cancer Registry, there are approximately 640 esophageal cancer cases in the 40‐ to 85‐year‐old age group annually (the crude rate in Taixing was 60.67 per 100,000). The study subjects were restricted to local inhabitants (Chinese Han race) aged 40–85 years who had lived in Taixing for at least 5 years prior to the diagnosis date for cases or the interview date for controls …”
Section: Methodsmentioning
confidence: 99%
“…The risk of ESCC increased with increasing number of affected relatives. In particular, cases of both parents being affected render an eightfold risk of ESCC for their offspring 48 . Previous epidemiological studies conducted in endemic areas (including mainly Linxian and Shanxi) in China demonstrated that individuals with a family history of esophageal cancer present a higher risk of such cancer 49,50 .…”
Section: Risk Factors Of Esccmentioning
confidence: 99%
“…To be more specific, offspring of two parents with ESCC has an eight-fold greater likelihood of developing ESCC than offspring of parents without ESCC. 14 Currently, genetic analyses of diseases, such as cancer, have focused on the detection of rare variants that may contribute to individual susceptibility to common complex diseases. 15 It is a matter of debate whether several DNA sequence variants with high penetrance are the major contributors to disease.…”
Section: Introductionmentioning
confidence: 99%